SERAPAN PHOSPOR TANAMAN JAGUNG (Zea mays L.) PADA PEMBERIAN DUA KOMPOS LIMBAH PERTANIAN DENGAN DOSIS YANG BERBEDA - nur chofifah (AGRONISMA, 2020)
The aim of this study was to determine the effects of different types of rice straw compost and soybean waste in different doses on the growth and efficiency of P uptake in maize plants. The design used was factorial RAK with control, the first factor was compost (P1 = rice straw; P2 = soybean oven), the second factor was dose (D1 = 5 tons · ha-1; D2 = 10 tons · ha-1; D3 = 15 tones, Ha-1; D4 = 20 tones, Ha-1) repeated three times. The results showed that rice straw compost with a dose of 5 tons. Ha-1 P1D1 treatment generally had an average plant height growth variable of 254.33 cm, a stem diameter of 16.11 mm, a number of leaves of 13.33 pot strands - 1 and 2 had leaf area of 6269.96 cm². In the P absorption efficiency, the variable P2 and D2 treatments have an average P intake value of 13.58 mg.kg-1 and a dose of 14.28 mg, kg-1 gave the optimal dose of straw compost 10.77 tons .ha-1 and soybean compost 13.13 ton.ha-1.